Estudo da liberação in vitro de captopril cápsulas magistrais por cromatografia líquida de alta eficiência - Azevedo, Roberta De Cássia Pimentel (2007)
Captopril is an anti-hypertensive and vasodilator agent utilized in the congestive cardiac insufficiency. Can be commercially found in Brazil in the form of tablets and compounded capsules. The aim of this study was to evaluate the dissolution profile of captopril in capsules obtained from compounded pharmacies (denominated A, B and C), when submitted to different conditions of pH, apparatus, stirring speed of dissolution media and analytical method. The validation of the dissolution procedure and the quantitation method were also evaluated. In the development of the dissolution test, several experimental conditions were tested: two dissolution media (0.1 M HCl and 0.01 M HCl, 900 ml), USP apparatus 1 and 2 and stirring speeds 50 and 100 rpm. Sample aliquots were withdrawn at 5, 10, 15, 20 and 45 minutes. The drug concentrations in dissolution medium were determined by liquid chromatography (HPLC) mobile phase mixture of phosphoric acid 0,11% (V/V) and methanol (45:55), UV detection at l 212 nm, C18 column, 5 mm, 25 ºC, at 1 ml/min flow rate and Rt around 1.76 min) and ultraviolet spectrophotometry (l 212 nm). The results showed that the chromatographic method was most suitable for captopril capsules evaluation, while the spectrophometric method (recommended by the Brazilian and the United States Pharmacopeias) presented low specificity. The chromatographic method is it possible to identify and to quantify the degradation product captopril disulfide, which may be present in captopril dosage forms. The dissolution procedure in the selected conditions was precise (pharmacy A RSD=4.05%, pharmacy B RSD=3.60% and pharmacy C RSD=2.85%), accurate (pharmacy A= 98.48%, pharmacy B= 98.80% and pharmacy C=99.04%), specific. The method was linear in the concentration range 15 mg/ml to 30 mg/ml (r=0,9996). With base in the statistical results pointed the selected conditions of dissolution test for capsules using, 900 ml of 0.01M HCl, basket apparatus, stirring speed 50 rpm, for 20 minutes showed better capacity of release drug assessed by HPLC. All capsules from participating compounding pharmacies presented satisfactory results in all tests assessed.